The Contribution of Agricultural Extension to Empowerment of Women for Agricultural Development - Shin Yee Siaw; Norsida Man; Nurul Nadia Ramli; Munifah Siti Amira Yusuf; Umar Abdulmumini (Journal of Agricultural Extension, 2024)
The study examined published works on the contribution of agricultural extension to the empowerment of women for agricultural development. It also explored the theoretical and practical implications. A systematic search in Scopus using relevant sets of keywords, including “agriculture extension”, “capacity building”, “women’s empowerment”, “women’s agency”, “women farmers”, “gender” and “agriculture”, identified 77 pertinent articles published between 1987-2023. The findings revealed that research on women’s empowerment in agriculture through capacity building had grown steadily since 1987, with leading journals being Gender, Technology and Development and the Journal of Agricultural Education and Extension. Quisumbing, Mudege, and Ponnusamy emerge as prolific authors, while India boasts the most distributed studies. Beyond a comprehensive review, this work introduces a novel concept for understanding women’s empowerment in agriculture. The concept comprised of five extension methods designed to empower women farmers, emphasising informed decision-making and leveraging the various forms of capital. The new conceptual framework aims to drive a collaborative approach towards achieving Sustainable Development Goal 5 – Gender Equality. Additionally, the review offers a comprehensive systematic review of gender studies, particularly in agriculture. It highlights the need for intercultural studies to examine the effectiveness of the proposed framework across diverse cultural contexts and regions.